An institutional analysis of the enforcement problems in merger control - Oliver Budzinski (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2010)
The literature identifies a significant drop in merger control enforcement activity on both sides of the Atlantic during the last decade. Furthermore, this drop in enforcement activity is convincingly connected to enforcement problems on the sides of the competition agencies. This paper goes beyond the identification of underenforcement and proceeds to the analysis of causes for the enforcement problems and the discussion of possible solutions. It argues that modern institutional economics suggest that a lack of 'fit' between the 'new' economic approach to merger control and the 'old' institutional environment of the legal enforcement procedures explains the drop of enforcement effectiveness on both sides of the Atlantic by implicitly raising the standard of proof, leading to unattainable standards, virtually eroding merger control enforcement power. As a consequence, the effects-based approach to merger control fails due to its failure to acknowledge its institutional implications. Reconciling industrial and institutional economics - promoting a comprehensive competition economics approach - however offers avenues towards an effective use of sophisticated industrial economic theories and methods. Firstly, incorporating economics into enforceable rules like strong rebuttable presumptions would adjust substantive merger control policy to the procedural institutional environment. Secondly, a reform of the standards of proof provisions would adjust the procedural framework to the characteristics of modern economic evidence and concepts. In summary, the enforcement problems in merger control require even more economic thinking, complementing industrial economic thought with institutional economic thought. I like to thank Arndt Christiansen and Eva Roth as well as the participants of research seminars at the Kiel Institute for the World Economy and at the Düsseldorf Institute for Competition Economics (DICE) for valuable comments on earlier versions of this paper.
Keywords: K21; L40; D02; 330; merger control; European competition policy; antitrust; enforcement problems; institutional economics; more economic approach; standard of proof; Fusionskontrolle; More Economic Approach; Wettbewerbspolitik; Kartellrecht; Rechtsdurchsetzung; Institutionalismus; EU-Staaten